Sistem Informasi Perpustakaan SMP HKBP Medan Berbasis Web Menggunakan Metode Framework For The Application System Thinking (FAST) - Gusti Masari Pangaribuan; Nikita Br. Nababan; Bremi Br Ginting; Nita Syahputri (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
One of the key components that helps the school's teaching and learning process is the library information system. The objective of this study is to apply the Framework for the Application of Systems Techniques (FAST) approach to the design and development of an online library information system for SMP HKBP Medan. This system is expected to increase efficiency in managing book data, borrowing and returning books as well as making it easier to access information for students and school staff. The use of the FAST method in developing this system involves several stages, including feasibility studies, needs analysis, system design, implementation, and evaluation. The result of this research is a web-based library information system that is user-friendly and able to improve the performance of the HKBP Medan Junior High School library.